Sosialisasi Computational Thinking Mata Pelajaran Bahasa Inggris untuk Guru-Guru MI dan MTs Wilayah Lombok Tengah - Diah Supatmiwati; Wiya Suktiningsih; Anthony Anggrawan; Katarina Katarina (LPPM Universitas Bumigora, 2021)
Computational thinking (CT) or in Indonesian called computational thinking is a method to train thinking skills in solving problems with reasoning and analysis, initially computational thinking is always related to computers. In fact, computational computing does not teach how to use computers or things that are always related to but the thought processes used to support problem science in all disciplines, mathematics, science, social studies, and languages, in this case the socialization of CT in learning English and Indonesian. Computational thinking can teach from an early age, starting from the elementary school level (SD) or the equivalent (MI) by making questions in English and Indonesian subjects by providing examples of simple problem solving found in basic language lessons. Through this community service, you can socialize CT to MI and MTs secondary school teachers in Central Lombok, the content is so that teachers can enter or enter CT into the subject they are taught, so that students are familiar with problems solving problems by means of computational thinking , the sustainable survival of computational thinking, a problem can be resolved properly, quickly and optimally.